Breast Cancer Detection and Treatment Monitoring Using a Noninvasive Prenatal Testing Platform: Utility in Pregnant and Nonpregnant Populations. (28th October 2020) - Lenaerts, Liesbeth; Che, Huiwen; Brison, Nathalie; Neofytou, Maria; Jatsenko, Tatjana; Lefrère, Hanne; Maggen, Charlotte; Villela, Darine; Verheecke, Magali; Dehaspe, Luc; Croitor, Anca; Hatse, Sigrid; et al.
Abstract: Background: Numerous publications have reported the incidental detection of occult malignancies upon routine noninvasive prenatal testing (NIPT). However, these studies were not designed to evaluate the NIPT performance for cancer detection. Methods: We investigated the sensitivity of a genome-wide NIPT pipeline, called GIPSeq, for detecting cancer-specific copy number alterations (CNAs) in plasma tumor DNA (ctDNA) of patients with breast cancer. To assess whether a pregnancy itself, with fetal cell-free DNA (cfDNA) in the maternal circulation, might influence the detection of ctDNA, results were compared in pregnant (n = 25) and nonpregnant (n = 25) cancer patients. Furthermore, the ability of GIPSeq to monitor treatment response was assessed. Results: Overall GIPSeq sensitivity for detecting cancer-specific CNAs in plasma cfDNA was 26%. Fifteen percent of detected cases were asymptomatic at the time of blood sampling. GIPSeq sensitivity mainly depended on the tumor stage. Also, triple negative breast cancers (TNBC) were more frequently identified compared to hormone-positive or HER2-enriched tumors. This might be due to the presence of high-level gains and losses of cfDNA or high ctDNA loads in plasma of TNBC. Although higher GIPSeq sensitivity was noted in pregnant (36%) than in nonpregnant women (16%), the limited sample size prohibits a definite conclusion. Finally, GIPSeq profiling of cfDNA during therapy allowed monitoring of early treatment response. Conclusions: The results underscore the potential of NIPT-based tests, analyzing CNAs in plasma cfDNA in a genome-wide and unbiased fashion for breast cancer detection, cancer subtyping and treatment monitoring in a pregnant and nonpregnant target population.